2005
DOI: 10.1183/09031936.05.00008504
|View full text |Cite
|
Sign up to set email alerts
|

Lung function, smoking and mortality in a 26-year follow-up of healthy middle-aged males

Abstract: Lung function has been associated with mortality after adjusting for other risk factors; however, few studies have adjusted for physical fitness and reported separate analyses according to smoking status.In 1972-1975, spirometry, clinical and physiological parameters were recorded in 1,623 apparently healthy males aged 40-59 yrs. After 26 yrs of follow-up, the current authors investigated the association between baseline lung function and mortality, adjusting for smoking, physical fitness and other potential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
88
4
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 49 publications
6
88
4
3
Order By: Relevance
“…In American and European populations, FEV 1 /FVC ratio and mortality often present significant relationships (2,(12)(13)(14), but in this study, we found no such relationship. This could be related to ratio and mortality differences, in addition to various anthropo-biological, social and cultural differences between Japanese and non-Japanese population.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…In American and European populations, FEV 1 /FVC ratio and mortality often present significant relationships (2,(12)(13)(14), but in this study, we found no such relationship. This could be related to ratio and mortality differences, in addition to various anthropo-biological, social and cultural differences between Japanese and non-Japanese population.…”
Section: Discussioncontrasting
confidence: 83%
“…Impaired lung function is a significant predictor of mortality (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). However, most of the studies showing this have focused mainly on forced expiratory volume in 1 second (FEV 1 ) (4)(5)(6)(7)(12)(13)(14) and a smaller number of such studies have focused on forced vital capacity (FVC), including FVC %perd.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies observed an association between pulmonary function and cardiovascular events, even after correcting for confounders like smoking [16][17][18][19][20]. Forced expiratory volume in one second (FEV 1 ) is a robust accurate index reflecting pulmonary physiology and is associated with a higher risk of dying from cardiovascular conditions [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Forced expiratory volume in one second (FEV 1 ) is a robust accurate index reflecting pulmonary physiology and is associated with a higher risk of dying from cardiovascular conditions [17,18].…”
Section: Introductionmentioning
confidence: 99%